Highly Stereoselective Intermolecular Haloetherification and Haloesterification of Allyl Amides - Soltanzadeh, Bardia (Angew Chem Int Ed Engl, 2015)
An organocatalytic and highly regio-, diastereo-, and enantioselective intermolecular haloetherification and haloesterification reaction of allyl amides is reported. A variety of alkene substituents and substitution patterns are compatible with this chemistry. Notably, electronically unbiased alkene substrates exhibit exquisite regio- and diastereoselectivity for the title transformation. We also demonstrate that the same catalytic system can be used in both chlorination and bromination reactions of allyl amides with a variety of nucleophiles with little or no modification.